The Contextualization of Hadith in Indonesia: Nusantara Ulema’s Response to Islamists - Alamsyah; Mahmudah, Siti; Huda, Syamsul (International Journal of Psychosocial Rehabilitation, 2020)
-The textual understanding of hadith is one of the causes of conflict among Muslims, that is also the case in Indonesia today. With textual method, the Indonesian islamism groups effort to realize the islamic state, establish the caliphate system, reject the democratic system, implement the formal shari’a and eliminate all things that are considered contrary to its. To respon it, the Moderate Indonesian Muslims, spearheaded by the Nusantara Ulema, strongly reject the textualism and re-understand the hadith by contextualization it’s content. This study examine the methods and motives of hadith contextualization by the Nusantara Ulema (the Archipelagic Ulema). The theory used is the Critical Discourse Analysis (CDA). This study found that the contextualization method used by the Nusantara Ulema was ta’lilul ahkam and maqashid. So the teachings of the hadith about the Khilafah, punishment for apostates, and heresy, for example, are interpreted and adjusted to current conditions. This research also found that the real motive behind the contextualization efforts by the Nusantara Ulema was to strengthen the plurality of the Unitary State of the Republic of Indonesia based on the Pancasila, and to maintain the traditions, rituals, practices, and ideology of the Nusantara Ulema based on Ahlussunnah wal Jama’ah from attacks by Islamists.